2014
DOI: 10.1002/2014jb011506
|View full text |Cite
|
Sign up to set email alerts
|

Gravity changes and deformation at Kīlauea Volcano, Hawaii, associated with summit eruptive activity, 2009–2012

Abstract: Analysis of microgravity and surface displacement data collected at the summit of Kīlauea Volcano, Hawaii (USA), between December 2009 and November 2012 suggests a net mass accumulation at 1.5 km depth beneath the northeast margin of Halema'uma'u Crater, within Kīlauea Caldera. Although residual gravity increases and decreases are accompanied by periods of uplift and subsidence of the surface, respectively, the volume change inferred from the modeling of interferometric synthetic aperture radar deformation dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 67 publications
(133 reference statements)
6
49
0
Order By: Relevance
“…We speculate that the rock mass containing the gas‐filled cracks from cluster 1 could represent material from the last collapse. The possible presence of void space inferred from gravity change data [ Bagnardi et al , ] also suggests a complex structure under the caldera, different than the simple picture of a spherical reservoir embedded in a homogenous rock mass. Most of the seismic events of the three clusters are located between sea level and 2 km bsl.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that the rock mass containing the gas‐filled cracks from cluster 1 could represent material from the last collapse. The possible presence of void space inferred from gravity change data [ Bagnardi et al , ] also suggests a complex structure under the caldera, different than the simple picture of a spherical reservoir embedded in a homogenous rock mass. Most of the seismic events of the three clusters are located between sea level and 2 km bsl.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in diverse volcanic settings have generally found magmatic activity to be associated with residual gravity variations of many tens to hundreds of microgals over years to decades. For example, increases in residual gravity at Kīlauea due to shallow magma accumulation were ~450 μGal during 1975–2008 (Johnson et al, ) and ~150 μGal during 2011–2012 (Bagnardi et al, ), and more than 400 μGal of change was associated with Etna's 1991–1993 eruptive episode (Rymer et al, ). A cumulative residual gravity decrease of up to 150 μGal during 1988–2010 was modeled as a combination of magma withdrawal and cooling/contraction of the magma reservoir at Askja, Iceland (de Zeeuw‐van Dalfsen et al, , ; Rymer et al, ), while an increase of ~140 μGal in the crater and 50–60 μGal on the flanks of Mount St. Helens between 2010 and 2016 was attributed in part to magma accumulation (Battaglia et al, ).…”
Section: Interpretation and Implicationsmentioning
confidence: 99%
“…Correlations between surface deformation and flux measurements from plume height have been observed for the 2010 Grímsvötn eruption, Iceland [Hreinsdóttir et al 2014] and applied in Japan [Kozono et al 2014], and this may be useful in future eruptions. In addition, surface deformation and gravity measurements can be coupled to constrain the nature of the pressurization source [e.g., Bagnardi et al 2014, Carbone et al 2015, or the magma reservoir processes responsible for variations in volume within the plumbing system , Parker et al 2016. Finally, strain fields can be used to reveal conduit geometry and provide constraints on the size of a reservoir and dike intrusions.…”
Section: Volcano Observationsmentioning
confidence: 99%